MY SAY: Soft power leadership - Abd Razak, Dzulkifli (2008)
Leadership seems to be among the hotly discussed issues of late, a subject of vital concern at all levels of organisations and nations. More so globally, what with a phenomenon called "Bush fatigue" which has set in, given the impending 2008 US presidential election on Nov 4. After all, for almost eight years now, the current US president George Bush has fallen short of global expectations, and in meeting world standards. This is in spite of Bush being the first US president to have an MBA degree! One would have thought that Bush would be the most adept in learning from the many worldclass US leadership gurus to whom the rest of the world look up to. One of them is Joseph S Nye Jr, who recently released a book titled The Powers to Lead (Oxford University Press 2008). Nye is university distinguished service professor at Harvard University's Kennedy School of Government, where he was formerly the dean. The author has also served in the US government in various capacities at high levels. He seems perfect to provide new leadership perspectives in addressing the present and future challenges.